Comparative overview of transfer pricing tax regulation in the world - Tanasić, Ljiljana (Anali Ekonomskog fakulteta u Subotici, 2020)
Along with the process of globalization and the increase of cross-border business, transfer pricing, as a medium of transactions between related legal entities, receives the epithet of one of the biggest challenges of national tax systems. However, the effects of individual actions of each country in the domain of addressing the potential risks of transfer pricing are largely limited, thus the emphasis is put on international cooperation and activities in terms of systemic resolution of the problem concerned. Based on the above, the paper shows comparative overview of the tax regulations of individual countries in the world (classified by continents) in the domain of using transfer pricing, stating whether international regulation applies on that basis or not and on which segments.